Intelligent planning and scheduling system - Hwang, Krystal Yan Lin (Nanyang Technological University, 2023)
This paper will document the front-end development of various Vehicle Routing Problem (VRP), i.e., Classical VRP (VRP), VRP with capacity constraints (CVRP), VRP with pick-up and delivery constraints (VRPDP), and VRP with time window constraints (VRPTW). The main goal is to visualize and animate the various VRP solutions through Hyper-Text Markup Language (HTML). The solution of the various VRPs will be saved in JavaScript Object Notation (JSON) format from Python for front-end to consume. The front-end which consists of HTML and JavaScript will process the solution and make use of Google Application Programming Interface (Google API) and OR tools to allow users to have an interactive view of shipment points and path routes taken by individual vehicles.